Comparison of Push-out Bond Strength of Gutta-percha to Root Canal Dentin in Single-cone and Cold Lateral Compaction Techniques with AH Plus Sealer in Mandibular Premolars - Hadi Mokhtari; Saeed Rahimi; Mohammad Forough Reyhani; Saeedeh Galledar; Hamid Reza Mokhtari Zonouzi (Tabriz University of Medical Sciences, 2015)
Background and aims. The single-cone technique has gained some popularity in some European countries. The aim of the present study was to compare the push-out bond strength of gutta-percha to root canal dentin with the single-cone and cold lateral compaction canal obturation techniques. Materials and methods. The root canals of 58 human mandibular premolars were prepared using modified crown-down technique with ProTaper rotary files up to #F3as a master apical file (MAF) and divided randomly into groups A and B based on canal obturation technique. In group A (n = 29) the root canals were obturated with single-cone technique with #F3(30/.09) ProTaper gutta-percha, which was matched with MAF in relation to diameter, taper and manufacturer; in group B (n = 29) the canals were obturated with gutta-percha using cold lateral compaction technique. In both groups AH plus sealer were used. After two weeks of incubation, three 2-mm slices were prepared at a distance of 2 mm from the coronal surface and push-out test was carried out. Data were analyzed with descriptive statistics using independent samples t-test. Results. There were statistically significant differences between two groups. The mean push-out bond strength was higher in group B (lateral compaction technique) compared to group A (single-cone technique; P < 0.05). Conclusion. Use of single-cone technique for obturation of root canals resulted in a lower bond strength compared to cold lateral compaction technique.